К вопросу о социальной роли и этике паблик рилейшнз - Королько, В. (Социология: теория, методы, маркетинг, 2000)
The article reviews pragmatic, conservative, radical, idealistic, neutral, critical, and vulgar-managerial worldview approaches to interpretation of public relationsí social role in a society widely spread in the theory and practice of Western countries. Sharing the American public relations theorist James Grunigís point of view on a normative theory of ethical PR, the author shows that only in case of practical application of symmetrical (ideal) model to mutual relation between organizations and publics the social institute of public relations may overcome a utilitarian approach to ethics andwill become effective and socially responsible indeed. The author comes to a conclusion, that the application of such a symmetrical model of public relations in Ukraine will promote the democracy development and the coming of a civil society in this country.